A Literature Review on Nutritional and Socioeconomic Determinants of Wasting in Toddlers - Jaizul W, Alim; AS, nurnisaa (Corespub, 2024)
This study aims to identify and analyze nutritional and socioeconomic factors that influence wasting in children under five through a systematic literature review. Wasting, or low weight for height, is a form of acute malnutrition that is common in children in developing countries and negatively impacts their physical and cognitive development. This study used data sources from various scientific articles published in the last 10 years and included studies related to nutritional factors, such as dietary diversity and micronutrient intake, as well as socioeconomic factors, including maternal education and family income. The review results showed that poor nutritional quality, limited access to health services, poor sanitation conditions, and low food security were the main determinants that increased the risk of wasting. These findings emphasize the need for a holistic approach to addressing wasting, including nutritional interventions, increasing access to health services, and educational programs for parents. This study provides recommendations for more integrated health policies to reduce the prevalence of wasting in children under five and improve their quality of life.